2012
DOI: 10.1099/mic.0.051946-0
|View full text |Cite
|
Sign up to set email alerts
|

Alternative routes of acetyl-CoA synthesis identified by comparative genomic analysis: involvement in the lipid production of oleaginous yeast and fungi

Abstract: For a bio-based economy, microbial lipids offer a potential solution as alternative feedstocks in the oleochemical industry. The existing genome data for the promising strains, oleaginous yeasts and fungi, allowed us to investigate candidate orthologous sequences that participate in their oleaginicity. Comparative genome analysis of the non-oleaginous (Saccharomyces cerevisiae, Candida albicans and Ashbya gossypii ) and oleaginous strains (Yarrowia lipolytica, Rhizopus oryzae, Aspergillus oryzae and Mucor circ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
91
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 108 publications
(101 citation statements)
references
References 54 publications
9
91
0
1
Order By: Relevance
“…Specifically, we contrasted the effects of leucine and isoleucine supplementation on lipogenesis and demonstrated that only leucine acts to promote lipogenesis. As Y. lipolytica possesses degradation pathways for both leucine and isoleucine to acetyl-CoA fatty-acid precursors [30][31][32] , leucine must act as an intracellular signal to permit lipid production, rather than as a carbon source. This is further established by the leucine-dependent TOR-inhibition phenotype of the PO1f leucine À uracil þ and PO1f leucine þ uracil þ strains (Supplementary Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Specifically, we contrasted the effects of leucine and isoleucine supplementation on lipogenesis and demonstrated that only leucine acts to promote lipogenesis. As Y. lipolytica possesses degradation pathways for both leucine and isoleucine to acetyl-CoA fatty-acid precursors [30][31][32] , leucine must act as an intracellular signal to permit lipid production, rather than as a carbon source. This is further established by the leucine-dependent TOR-inhibition phenotype of the PO1f leucine À uracil þ and PO1f leucine þ uracil þ strains (Supplementary Fig.…”
Section: Discussionmentioning
confidence: 99%
“…1a). Leucine biosynthetic capacity has also been implicated as an effector of lipogenic ability in oleaginous organisms 25,29 , and a putative acetyl-CoA-generating leucine degradation pathway was recently identified through a comparative genomics analysis of non-oleaginous and oleaginous yeast strains 30 . In this regard, Y. lipolytica also possesses homologues for every enzyme and enzymatic subunit necessary for acetyl-CoA generation through isoleucine degradation (445% similarity to Homo sapiens enzymes) 31,32 .…”
mentioning
confidence: 99%
“…It has been reported that Leu metabolism is involved in the generation of the acetyl-CoA required for fatty acid biosynthesis in the oleaginous fungus Mucor circinelloides (Vorapreeda et al, 2012;Rodríguez-Frómeta et al, 2013). In addition, catabolism of amino acids such as Ala and Gln could provide carbon skeletons directed to fatty acid elongation (Schwender et al, 2006;Junker et al, 2007;Hockin et al, 2012).…”
Section: Bcca Catabolism Affects Tag Biosynthesismentioning
confidence: 99%
“…After 5 days of incubation, Sudan Black-stained smears from each culture were observed under optical microscopy looking for the presence of intracellular blue oil globules which are characteristic of oleaginous yeasts. Non oleaginous yeast (Saccharomyces cerevisiae) was used as a negative control [8]. For the oleaginous isolates, intracellular content of saponifiable lipids was quantified as described by Burja et al [9] with modifications.…”
Section: Screening For Oleaginous Yeastsmentioning
confidence: 99%
“…Intracellular saponifiable lipids were evaluated daily from the second to the sixth day. Ammonia was determined using the commercial kit UREA/BUN-COLOR (Biosystems COD 11536) and nitrate was analyzed by HPLC with a IC-Pack Anion column (Waters) maintained at 40 °C, using phosphate buffer (0,01 M, pH 6,8) as mobile phase at a flux of 1,2 mL min -1 and a UV detector (Shimadzu SPD-10AV UV-VIS Detector) at 210 nm. Glycerol was determined by HPLC using an Aminex HPX-87C (Bio-Rad), 250 x 4 mm column, at 67 °C with water as mobile phase and a RID-10A Shimadzu detector.…”
Section: Intracellular Lipid Accumulation In Presence Of Glycerolmentioning
confidence: 99%